HUBUNGAN KETERAMPILAN MENGAJAR GURU PENDIDIKAN AGAMA KRISTEN DENGAN HASIL BELAJAR SISWA KELAS VIII SMP NEGERI 1 PORSEA - Asnija Malau (IAKN Tarutung, 2018)
Abstract, This Research aim to to know the Skill Teach The Teacher of Christian Education With The Result Learn The Student of Class of VIII SMP Country 1 Porsea. With the hypothesizing [of] there are [relation/link] which are positive and signifikan [of] [among/between] Skill Teach The Teacher of Christian Education With The Result Learn The Student of Class of VIII SMP Country 1 Porsea. Research Population amount to 218 people and sampel taken [by] 20% amounting to 38 people. Data collected with the enquette closed [by] as much 25 item. And have diujicoba with the test of validity and reliabitasnya. Result of data analysis indicate that there are [relation/link] which are positive and signifikan [of] [among/between] Skill Teach The Teacher of Christian Education With The Result Learn The Student of Class of VIII SMP Country 1 Porsea of Regency of Toba Samosir of Study Year 2017 / 2018 with the correlation coefficient [of] r count r tables of or 0,507 0,320 and test the signifikan relation obtained [by] t count t tables of equal to 3,533 2,029, inferential thereby Ho refused and [Is] ha accepted